EFEKTIVITAS MODEL PEMBELAJARAN PBL BERBANTUAN MEDIA FLIPBOOK SIRPA DALAM MENINGKATKAN PEMAHAMAN IPAS SISWA KELAS V - Sari, Intan Kumala; Ardianti, Sekar Dwi; Setiawaty, Rani (Jurnal Dedikasi Pendidikan, 2025)
This research aims to determine the difference in the average value of science understanding before and after using the PBL learning model assisted by SIRPA flipbook media and determine the increase in science understanding by implementing the PBL learning model assisted by SIRPA flipbook media. This research is quantitative research with a pre-experimental type of research. The design of this research is One Group Pretest Posttest. In this research, data collection techniques used observation, interviews and tests. The data analysis technique used is the paired sample t-test and the N-Gain test. The results of the research prove that the PBL learning model assisted by SIRPA flipbook media makes a difference and increases understanding of IPAS as shown by the results of the paired sample t-test, which obtained a Sig value of 0.000 < 0.05. Furthermore, the N-Gain test results obtained a value of 0.4252 which is in the range 0.3 < N-Gain < 0.7 with medium criteria. Based on the research results, the use of the PBL learning model assisted by SIRPA flipbook media is effective in increasing fifth grade students' understanding of science and science